You are on page 1of 35

Fakultät Informatik – Institut für Systemarchitektur – Professur Rechnernetze

Functions of One Random Variable
Waltenegus Dargie
Chair for Computer Networks
Slides are based on the book book: A. A Papo Papoulis lis and S S.U. U Pillai Pillai, "Probability, random variables and stochastic processes", McGraw Hill (4th edition), 2002.

Introduction
• Let X be a random variable defined on the ) and model d l (Ω, F , P ), d suppose g(x) is i a function of the variable x. Define Y = g ( X ). • Is Y necessarily a random variable? If so what is its PDF FY ( y ) ? • If Y is a random variable, then for every B Borel l set t B, the th set t of fξ f for which hi h Y (ξ ) ∈ B must belong to F.
P (Y ∈ B ) = P ( X ∈ g −1 ( B )).
2

Introduction
• Particularly,
FY ( y ) = P (Y (ξ ) ≤ y ) = P (g ( X (ξ )) ≤ y ) = P (X (ξ ) ≤ g −1 ( −∞, y ]).

• Th Thus the th distribution di t ib ti function f ti as well ll as the density function of Y can be d t determined i d in i terms t of f that th t of f X. • To obtain the distribution function of Y, we must determine the Borel set on the x-axis −1 X ( ξ ) ≤ g ( y ) for every given y, and such that the probability of that set.
3

X⎜ fY ( y) = If • C Combining bi i the th two t density d it functions f ti yields: 1 y −b fY ( y) = ⎛ ⎞ fX ⎜ ⎟. Y a ⎠ ⎝ 1 ⎛ y −b ⎞ ⎛ y −b⎞ = 1 − FX ⎜ . Y = aX + b If a > 0 . |a| ⎝ a ⎠ y −b⎞ ⎛ ( ) ( ) F ( y ) = P Y ( ξ ) ≤ y = P aX ( ξ ) + b ≤ y = P X ( ξ ) > ⎜ ⎟ a < 0. y −b⎞ ⎛ ⎛ y −b⎞ FY ( y) = P(Y (ξ ) ≤ y ) = P(aX (ξ ) + b ≤ y ) = P⎜ X (ξ ) ≤ = F ⎟ ⎟. f y = − fX ⎜ ( ) ⎟.Examples A. ⎟ Y a ⎝ a ⎠ ⎝ a ⎠ 1 ⎛ y −b⎞ fX ⎜ ⎟. a ⎝ a ⎠ ⎝ a ⎠ ⎝ a ⎠ 4 .

y < 0. ⎩ ( y) . x1 x2 Y = X2 y FY ( y ) = 0. Y = X 2 FY ( y ) = P (Y (ξ ) ≤ y ) = P (X 2 (ξ ) ≤ y ). and For d hence h X For y > 0 . F y < 0 .Examples B. ) y > 0. y > 0. { X 2 (ξ ) ≤ y}= φ . Hence: {Y (ξ ) ≤ y } = { X 2 (ξ ) ≤ y } ≡ {x1 < X (ξ ) ≤ x 2 } FY ( y ) = P ( x1 < X (ξ ) ≤ x 2 ) = F X ( x 2 ) − F X ( x1 ) = FX ( y ) − FX ( − y ). diff ti ti we get: t ⎧ 1 f ( y ) + f X (− ⎪ fY ( y ) = ⎨ 2 y X ⎪ 0. otherwise . 5 . • By B di direct t differentiation.

so that fX (x) = fY ( y ) = 1 − x2 /2 e .Examples • If f X ( x) represents an even function. ) • In particular if X ∼ N ( 0 . then th expression the i above b reduces d to t fY ( y ) = 1 fX y ( y ) U ( y ).1). ) 2π y 6 . 2π 1 e − y / 2U ( y ).

⎩ X > c. • Similarly y < 0 . = X (ξ ) + c FY ( y ) = P (Y (ξ ) ≤ y ) = P ( X (ξ ) + c ≤ y ) y < 0. g( X ) −c c X • In this case P (Y = 0) = P ( − c < X (ξ ) ≤ c ) = FX ( c ) − FX ( − c ). • For y > 0 . ⎪ Y = g ( X ) = ⎨ 0. if x < − c . X ≤ − c. 7 . ⎧ X − c. y > 0. − c < X ≤ c. we have x > c .Examples C. ⎪ X + c. and Y (ξ ) = P ( X (ξ ) ≤ y − c ) = FX ( y − c ). and Y (ξ ) = X (ξ ) − c FY ( y ) = P (Y (ξ ) ≤ y ) = P ( X (ξ ) − c ≤ y ) = P ( X (ξ ) ≤ y + c ) = FX ( y + c ).

⎧ f X ( y + c ).Examples • Subsequently. ⎪ f Y ( y ) = ⎨[ FX ( c ) − FX ( − c )]δ ( y ). ⎩ X FX ( x ) FY ( y ) x y 8 . ) y=0 ⎪ f ( y − c ). y > 0. y < 0.

⎩ = f X ( y )U ( y ) + FX (0)δ ( y ). g ( x) = ⎨ ⎩ 0. 9 . ⎪ 0. ) For y > 0 . Y = g ( X ).Examples D. x > 0. ⎪ f Y ( y ) = ⎨ FX (0)δ ( y ) y = 0. Thus y > 0. x ≤ 0. ⎧ x. ⎧ f X ( y ). y < 0. Y X P (Y = 0) = P ( X (ξ ) ≤ 0) = FX ( 0). FY ( y ) = P(Y (ξ ) ≤ y ) = P( X (ξ ) ≤ y ) = FX ( y ). Y = X .

so that FY ( y) can be nonzero only l in i a < y < b. If so. given Y = g ( X ). (1) Sketch the graph y = g ( x ). (2) Determine whether there are discontinuities in the range space of y. and d for f y > b. FY ( y) = 0. • For example. evaluate e a uate P(Y (ξ ) = yi ) at t these ese discontinuities. FY ( y) = 1. 10 .Continuous Random Variables • Generally. if a < y < b is the range space ) Then of f y = g ( x ). Th for f y < a. and determine the range space of y.

Continuous Random Variables • In the continuous region of y. (3) Compute FY ( y ) for −∞ < y < +∞. use the b i approach basic h FY ( y ) = P (g ( X (ξ )) ≤ y ) and d determine appropriate events in terms of th random the d variable i bl X for f every y. and obtain fY ( y ) = dFY ( y ) dy in a < y < b . 11 .

if Y = g( X ) is a continuous f function. and it eventually becomes monotonic as | x |→ ∞.Continuous Random Variables • However. has only a finite number of maxima and minima. 12 . ti it i is easy t to establish t bli h a di direct t procedure to obtain fY ( y). • A continues function g(x) with g′(x) nonzero at all but a finite number of points.

13 . b l g ( x) y + Δy y x x 1 x1 + Δx1 x2 + Δx2 x 2 x 3 x3 + Δx3 P {y < Y (ξ ) ≤ y + Δ y } = ∫ y + Δy y f Y ( u ) du ≈ f Y ( y ) ⋅ Δ y .Continuous Random Variables • Consider a specific y on the y-axis and a positive iti increment i t Δ y as shown h below.

Continuous Random Variables • But the Event {y < Y (ξ ) ≤ y + Δ y } can also be expressed d in i terms t of f X (ξ ) . the random variable X could be in any y one of the three mutually exclusive intervals: {x1 < X (ξ ) ≤ x1 + Δx1}. • As can be seen in the figure. . • As a result when {y < Y (ξ ) ≤ y + Δ y }. x3 for the specific y chosen there. the equation y = g(x) has three solutions x1 . {x2 + Δx2 < X (ξ ) ≤ x2} or {x3 < X (ξ ) ≤ x3 + Δx3}. x2 . • Hence: P {y < Y (ξ ) ≤ y + Δ y } = P { x 1 < X (ξ ) ≤ x 1 + Δ x 1 } 14 + P { x 2 + Δ x 2 < X (ξ ) ≤ x 2 } + P { x 3 < X (ξ ) ≤ x 3 + Δ x 3 } .

we get and Δx3 > 0.Continuous Random Variables • For small Δy. fY ( y ) = ∑ i 1 1 f X ( xi ) = ∑ f X ( xi ). fY ( y ) Δy = f X ( x1 ) Δx1 + f X ( x2 ) (−Δx2 ) + f X ( x3 ) Δx3 . • In this case. dy / dx x i g ′( xi ) i 15 . Δxi . Δx1 > 0. that: • As Δx2 < 0 so | Δxi | 1 fY ( y ) = ∑ f X ( xi ) =∑ f X ( xi ) Δy i i Δy / Δxi Δy → 0.

y > 0. otherwise ⎩ 16 ( ) . ⎪ fY ( y ) = ⎨ 2 y ⎪ 0. Moreover 2 x1 = − y . y > 0. x2 = + y dy y dy y = 2 x so that th t =2 y dx dx x = xi Y = X2 y • Hence: x1 x2 X ⎧ 1 f X ( y ) + f X (− y ) . for • Moreover.Continuous Random Variables • If Y = X .

2 2 α +x − ∞ < y < +∞ . ⎟ X⎜ 2 ⎜ ⎟ y ⎝ y⎠ x = x1 • If X is a Cauchy random variable f X ( x) = 1 α /π (1 / α ) / π fY ( y ) = 2 2 = . − ∞ < x < +∞. X x1 = 1 / y • Here for every y. sol tion and solution. 2 2 2 (1 / α ) + y y α + (1 / y ) α /π . dy 1 = − 2 so that d dx x is the only = 1 2 = y . 2 1/ y dy d dx • Hence: fY ( y ) = ⎛1⎞ 1 f . 17 .Continuous Random Variables • If Y = 1 .

x = xi 18 . x1 .1). x3 .Continuous Random Variables • Suppose f X ( x ) = 2 x / π 2 .π ). fY ( y ).L. • For 0 < y < 1. x2 . and Y = sin X . the equation x1 = sin −1 y has an L. y = sin x has zero probability of falling outside the interval ( 0 . 0 < x < π . lid ) • Note ote also a so because o of the t e sy symmetry: et y x2 = π − x1 dy = cos x = 1 − sin 2 x = 1 − y 2 dx dy dx = 1− y2 . i fi it number infinite b of f solutions l ti where y = sin x is the principal solution (ref. t th to the next t slide). D t Determine i • Since X has zero probability of falling outside the interval (0.

(a) y =s sin x π x3 x y x −1 x1 x2 π x3 x (b) • But from the figure (b).Continuous Random Variables • Hence. for 0 < y < 1. 19 . f X ( x−1 ) = f X ( x3 ) = f X ( x4 ) = L = 0 (Except for f X ( x1 ) and f X ( x 2 ) the rest are all zeros). fX (x) fY ( y ) = i = −∞ ∞ i ≠0 ∑ +∞ 1 1− y 2 f X ( x i ).

otherwise. ⎩ fY ( y ) 2 π y 1 20 .Continuous Random Variables • As a result: fY ( y ) = 1 1 − y2 ( f X ( x1 ) + f X ( x2 ) ) = ⎛ 2 x1 2 x 2 ⎞ ⎜ 2 + 2 ⎟ 2 π ⎠ 1− y ⎝ π 1 0 < y < 1. = 2 ( x1 + π − x1 ) π 2 1 − y2 2 ⎧ . ⎪ 2 = ⎨π 1 − y ⎪ 0.

x1 = tan−1 y is the principal solution. y moves mo es from (− ∞ . + ∞ ) . dx dx 21 . π / 2) . dy d tan d t x = = sec 2 x = 1 + tan 2 x = 1 + y 2 . • As x moves mo es from (−π / 2.Continuous Random Variables • Let Y = tan X Determine where fY ( y ). X ∼U (− π / 2. Hence. = tan X is one-to-one • For any y. π / 2 ) . • The function Y for −π /2< x <π /2.

• Which represents a Cauchy density function with σ = 1. | dy / dx |x = x1 1 + y2 − ∞ < y < +∞ . 1 f X ( x) y = tanx −π /2 fY ( y ) = 1 1 + y2 y −π /2 π /2 x x1 π / 2 (b) x (c) 22 y (a) .Continuous Random Variables • Therefore: fY ( y ) = 1 1/π f X ( x1 ) = .

L i i 1 2 i ) • And Y = g ( X ).L 23 .L. y = y1 . x . yi . • Clearly Y is also of discrete-type discrete-type. yi = g ( xi ).Discrete Random Variables • Suppose X is a discrete-type random variable with P( X = x ) = p . and when x = xi . x .L. y2 . and for all yi P(Y = yi ) = P( X = xi ) = pi . x = x .

24 . k 2 + 1. L . 2.Discrete Random Variables • Suppose • For X ∼ P ( λ ). k = 0. −λ so that . 5.L P( X = k ) = e λk k! Y = X 2 + 1.2.L. For j = k 2 + 1 P(Y = j ) = P X = ( j − 1 = e− λ ) λ j −1 ( j − 1)! .1. • As X takes the values0 . find the PMF of Y. L. L . k .1.L. j = 1. k + 1. L and takes the value P(Y = k 2 + 1) = P( X = k ) . 2. 2 .5. Y 2 1.

d.d. i f ti it is desirable to characterize the random variable i bl i in terms t of f its it average behavior.f f X ( x) provides id complete l t information i f ti about b t it. it and for any Borel set B on the x-axis P ( X (ξ ) ∈ B ) = ∫ B f X ( x ) dx .Mean • For a random variable X. b h i • The mean and variance are often used to represent the overall properties of the random a do variable a ab e and a d its ts p. • Si Since f X ( x) represents t detailed d t il d information.f. its p. pd 25 .

26 .Mean • The Mean or the Expected Value of a R d Random variable i bl X is i defined d fi d as: ηX = X = E( X ) = • For a discrete X: i ∫ +∞ −∞ x f X ( x ) dx . η X = X = E ( X ) = ∫ x ∑ piδ ( x − xi ) dx = ∑ xi pi ∫ δ ( x − xi ) dx i 14 4244 3 1 = ∑x p =∑x i i i i i P ( X = xi ) . • Mean represents the average value of the random variable in a very large number of trials.

Mean (a) Mean of X ~ U (a. b) E(X ) = x 1 x dx = b−a b−a 2 2 b ∫ b a a b2 − a2 a +b = = 2(b − a ) 2 (b) Mean of Exponential with parameter λ E(X ) = ∫ ∞ 0 x λ e −x /λ dx = λ ∫ ye − y dy = λ . 0 ∞ (c) Mean of Poisson with parameter λ E(X ) = ∑ ∞ kP ( X = k ) = k =0 −λ ∑ ∞ ke −λ −λ λk k! = e −λ k =0 ∑ ∞ k λk k! k =1 = e ∑ ∞ λk ( k − 1 )! = λe k =1 ∑ ∞ λi i! = λ e −λ e λ = λ . 27 i=0 .

+ μ ⋅ ∫ 2 ∫ −∞ − ∞ 14 42 4 4 3 πσ 12 4 4 42 4 4 43 0 2 2 1 28 . =∑ p q = np ∑ k =1 ( n − k )! ( k − 1)! i = 0 ( n − i − 1)! i! n n • Mean of a normal distribution E(X ) = = 1 2πσ 1 2πσ 2 ∫ +∞ −∞ +∞ xe − ( x − μ ) 2 / 2σ 2 dx = 1 2πσ 1 2 ∫ +∞ −∞ +∞ ( y + μ )e 2 2 − y 2 / 2σ 2 dy 2 − y / 2σ − y / 2σ ye dy e dy = μ .Mean • Mean of a binomial distribution n ⎛ n ⎞ k n−k n! k n−k = p q k p q E ( X ) = ∑ kP ( X = k ) = ∑ k ⎜ ⎟ ∑ ⎜k ⎟ ( n − k )! k ! k =0 k =0 ⎝ ⎠ k =1 n n −1 ( n − 1)! n! k n−k p i q n − i −1 = np ( p + q ) n −1 = np .

supposeY = g ( X ) defines a new random variable with ).f fY ( y ) p • Then. since. • If E (Y ) is the only quantity of interest.d. μY is given by: μ Y = E (Y ) = ∫ +∞ −∞ y f Y ( y ) dy .Mean of g(X) • Given X ∼ f X ( x ). p. i where xi represent the multiple solutions of y = g(xi) and Δy > 0 . since P ( y < Y ≤ y + Δy ) = ∑ P (xi < X ≤ xi + Δxi ) . 29 . we don’t need to first compute fY(y).

E (Y ) = E (g ( X ) ) = E (Y ) = ∫ +∞ −∞ y f Y ( y ) dy = ∫ +∞ −∞ g ( x ) f X ( x ) dx . . ∑y i f X ( x i )Δ x i = ∑ g(x ) f i i X ( x i )Δ x i . xi + Δxi ) terms form nonoverlapping pp g intervals. • In the discrete case. i ∑ f X ( x i )Δ x i . Hence. fY ( y ) Δ y = where the (xi . 30 . ∑ g ( x )P ( X i i = x i ).Mean of g(X) • The expression above can also be rewritten itt as. y fY ( y ) Δ y = • As Δy → 0.

and X is a Poisson random variable. E (X 2 )= ∑ k k =0 ∞ 2 P(X = k) = ∑k k =0 −λ ∞ 2 e −λ λk k! = e −λ ∑k k =1 ∞ 2 λk k! = e −λ ∑ k ( k − 1)! k =1 ∞ λk = e ∞ ∑ ( i + 1) i=0 −λ ∞ λ i +1 i! = λe −λ ⎛ ∞ λi ⎜ ⎜ ∑ i i! + ⎝ i=0 ∑ λi ⎞ i=0 ⎟ = λe ⎟ i! ⎠ ⎛ ∞ λi λ ⎞ ⎜ ⎜ ∑ i i! + e ⎟ ⎟ ⎝ i =1 ⎠ ∞ ⎛ ∞ λi λ m +1 −λ ⎛ λ ⎞ λ ⎞ ⎟ ⎜ ⎟ = λe ⎜ + e = λ e + e ∑ ⎜ ∑ ( i − 1 )! ⎟ ⎜ ⎟ ) ⎝ i =1 ⎠ ⎝ m =0 m! ⎠ = λ e − λ (λ e λ + e λ ) = λ 2 + λ .Mean of g(X) • Suppose Y = X2. find E(Y). −λ 31 .

. • Though g both of them have the same mean.f d f of f a random d variable i bl • Consider two Gaussian random variables: X 1 ~ N (0.1) and X 2∼ N (0.fs are quite different.10). their p. f X 1 ( x1 ) f X 2 ( x2 ) x1 (a) ( ) σ 2 =1 (b) ( ) σ 2 = 10 32 x2 .Variance • Mean alone will not be able to truly represent t the th p.d.d.

• Since this deviation can be either positive or negative. X − μ represents t th the deviation d i ti of f the th random d variable from its mean. 2 X +∞ −∞ 33 . the quantity ( X − μ ) 2 .Variance • For a random variable X with mean μ . and its average value E [ ( X − μ ) 2 ] represents the average mean square deviation of X around its mean. 2 2 ( ) σ = E [ X − μ ] > 0 with g ( X ) = ( X − μ ) 2 • If we define X σ = ∫ ( x − μ ) 2 f X ( x )dx > 0.

Var ( X ) = σ = 2 X +∞ −∞ = 2 ∫ (x +∞ −∞ 2 − 2 x μ + μ 2 ) f X ( x ) dx +∞ −∞ ∫ x f X ( x ) dx − 2 μ ∫ 2 x f X ( x ) dx + μ 2 2 • For example example. the variance of a Poisson random variable is given by: σ 2 X = E (X )− μ 2 = E (X 2 ) − [E ( X ) ] = X −X . 2 ___ 2 = X −X ___ 2 2 = (λ 2 + λ ) − λ 2 = λ .Variance • Expanding the expression in the previous slide results. 34 .

• Using the identity • Diff Differentiating ti ti both b th sides id of f the th above b expression w. Var ( X ) = E [( X − μ ) 2 ] = 2 ( ) x − μ ∫ −∞ +∞ 1 2 πσ 2 2 e − ( x − μ )2 / 2σ 2 dx .t.Variance • The variance of the normal random variable. −∞ 2 ∫ +∞ 1 e − ( x − μ )2 / 2σ dx = 1 ∫ +∞ −∞ +∞ ( x − μ )2 σ 3 e − ( x − μ )2 / 2σ 2 dx = 2 2π 2 2 ( ) x − μ ∫ −∞ 1 2 πσ 2 e −( x−μ ) / 2σ d =σ dx 2 (6-22) 35 .r. σ yields: ∫ ∫ +∞ −∞ +∞ f X ( x ) dx = −∞ e − ( x − μ )2 / 2σ 2 2 πσ dx = 2 π σ . i bl N ( μ . σ 2 ).